Vertical Nanowire Electrode Arrays as Novel Electrochemical Label‐Free Immunosensors. Issue 24 (11th February 2015) - Nasr, Babak; Chana, Gursharan; Lee, Ting Ting; Nguyen, Thanh; Abeyrathne, Chathurika; D'Abaco, Giovanna M.; Dottori, Mirella; Skafidas, Efstratios
<x xml:space="preserve">Abstract</x> A new method for the fabrication of a label‐free electrochemical immunosensor based on vertical nanowires (VNWs) is proposed. The VNWs are functionalized to detect antibodies against a major astrocytic structural protein component, glial fibrillary acidic protein (GFAP). It is revealed that the interaction of GFAP‐antibody with functionalized VNWs leads to a clear change in device conductance and the corresponding capacitance.